'It's working together with what you've got': Healthcare professionals' experiences of working with people with combined intellectual disability and personality disorder diagnoses. Issue 6 (20th June 2022) - Zarotti, Nicolò; Hudson, Clive; Human, Hannah‐Rose; Muratori, Greco; Fisher, Paul
Abstract: Background: People with intellectual disability often receive diagnoses which may complicate their clinical care. Among these, personality disorder diagnoses are still considered contentious. Little is also known on the perspectives of staff caring for people with intellectual disability who have received a personality disorder diagnosis. Methods: Three focus groups were carried out to explore 15 healthcare professionals' subjective experiences of working with people with intellectual disability who also have a recorded additional diagnosis of personality disorder. Data were analysed through thematic analysis. Findings: Four overarching themes were identified: (a) diagnostic issues and the need for person‐centred approaches; (b) challenges and adjustments to working with combined intellectual disability and PD diagnoses; (c) the importance of multidisciplinary team training, support, and cohesion; (d) provision issues and barriers to service access. Conclusions: The themes are outlined in depth and a number of implications for clinical management and service improvement are discussed.